Surabaya Youth Political Discourse in in the Dynamics of Election Information - Maya Mustika Kartika sari,; Agus Satmoko Adi,; Mi’rojul Huda,; Warsono, (Technium Social Sciences Journal, 2023)
Youth have become the main agents of change and are usually the most affected by changes in the socio-political context in Indonesia. The very large youth population in Indonesia signifies a great asset for socio-political transformation in the democratic space. Specifically, this study examines youth political discourse in the changes and dynamics of the 2024 General Election. This study aims to identify linguistic expressions of public practice within the scope of youth political culture in Surabaya. Exploration of the relationship between different sets of influences and different types of political activism seeks to contribute to a better understanding of the reasons why young people choose certain paths of political participation regarding the 2024 election. Focus group discussion methods and in-depth interviews are considered most appropriate on the basis of the advantage is in gaining in-depth insights into the respondents' experiences regarding their understanding and conception of the 2024 election. Then a discourse analysis is carried out by comparing the knowledge from general cultural knowledge shared by participants from various social groups and knowledge shared by participants from separate social groups.